ENVIRONMENTAL SAFETY IN GAS PROCESSING PLANTS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Environmental safety has become a critical factor in the design of gas processing facilities due to increasing environmental regulations, climate change concerns, and public awareness. Modern gas processing plants must minimize harmful emissions, reduce waste generation, and ensure sustainable use of natural resources. This article analyzes contemporary engineering approaches and innovative technologies aimed at improving environmental safety during the design stage of gas processing facilities. Emphasis is placed on emission control systems, waste minimization strategies, digital monitoring technologies, and compliance with international environmental standards. The results demonstrate that integrating environmental considerations into early design stages significantly enhances sustainability and operational efficiency.
Keywords: Gas processing facilities, environmental safety, sustainable design, emission control, environmental engineering.